The Analysis of the Digitalization Role on Towards Supply Chain Resilience and Sustainable (Case Study: MSME in Balikpapan City) - Kurnia, Wahyu Ismail; Harits, Dimaz; Cahyo, Winda Nur (Spektrum Industri, 2025)
The COVID-19 pandemic has caused significant changes in almost all sectors, including disruptions in the global supply chain. Acceleration of supply chain recovery to create supply chain resilience and sustainability by implementing various strategies, including digitalization. Empirical evidence is still very limited in the literature, especially in studies involving supply chain actors from MSMES with different characteristics and locations. Therefore, this study aims to address this problem by analysis the role of digitalization in improving supply chain resilience and sustainability based on a case study of MSMES in Balikpapan City. Three hypotheses have been proposed to answer the research problem. This study uses the Structural Equation Modelling (SEM) approach with the help of IBM AMOS software version 22 for hypothesis testing. Questionnaires were distributed to 200 MSME actors with different characteristics in Balikpapan City. The results are: (1) the role of digitalization has a significant positive effect on supply chain resilience; (2) the role of digitalization has a positive effect on supply chain resilience; (3) supply chain resilience has a significant positive effect on supply chain sustainability. Despite the differences in characteristics of business models and business sectors, supply chain resilience and sustainability can be improved by using appropriate digital technology in each supply chain. The contributes of this study shows that there is a potential for good supply chain visibility that allows every actor along the supply chain to monitor, transfer, and improve the accuracy of decision making accurately and quickly, to handle any disruptions and improve supply chain sustainability.